Impact of the COVID‐19 Pandemic on Dementia Caregivers in the South US. (20th December 2022) - Starks, Takiyah D.; Lloyd, Shawnta'; Caban‐Holt, Allison M; Clark, Jarrel; Byrd, Goldie S.
Abstract: Background: Compared to their non‐caregiving peers, caregivers of persons with dementia (PWD) endure higher psychological distress, social isolation and increased morbidity and disability. Stress and isolation experienced by caregivers during the COVID‐19 pandemic have added to caregiver burden and worsened health. The objective of this study was to obtain a greater understanding of the health and needs of informal caregivers of PWD during the COVID‐19 pandemic. Method: Using a cross‐sectional questionnaire, we attained demographic data, characteristics of caregiving during the COVID‐19 pandemic, mental health status, COVID‐19 testing and illness, and protective measures taken to prevent infection with COVID‐19 among caregivers of PWD. From March 2021 to August 2021, respondents were recruited through the Maya Angelou Center for Health Equity's Alzheimer's disease (AD) registry. Descriptive statistics (frequency and proportions) of demographic, caregiving, health, and COVID‐19 related data for caregivers of PWD was conducted using SAS® software version 9.4. Result: A total of 274 caregivers of PWD participated in the study. More than half of caregivers were women (56.57%), and approximately 73% of caregivers were married. The racial composition of the majority of caregivers included African American (44.16%), Non‐Hispanic White (26.64%), and Native American (20.44%). Most caregivers were providing care for parents (59.86%) or a partner (21.17%). Nearly 46% of caregivers reported experiencing stress, but not being burnt out. Almost 47% of caregivers reported high psychological distress during the COVID‐19 pandemic. In addition to caregiving stressors due to the COVID‐19 pandemic, caregivers also experienced behavioral changes in their household; more than half of caregivers experienced increased interpersonal conflict with loved ones, friends, or co‐workers. The top 3 needs reported during the COVID‐19 pandemic included support with caregiving, medical care, and food. Conclusion: Approximately half of caregivers of PWD experienced stress and psychological distress during the COVID‐19 pandemic. In addition to the stress of caregiving, caregivers lacked support for necessary medical services and social needs. The data collected from caregivers during the COVID‐19 pandemic will be used to develop recommendations to support informal caregivers during emergency situations.